Znaczenie prawa własności intelektualnej w przemyśle modowym - Guss, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The fashion industry is characterized by a fast pace of changes and very dynamic development. Designers annually introduce several collections, each of them containing a few dozen silhouettes, which makes it extremely difficult to provide effective legal protection for their projects. In effect designs reminiscent of those presented on the catwalk appear, which currently, in the era of the Internet and social media, is happening quickly, often even before designer collections go on sale. Due to the lack of legal regulations created specifically for the fashion industry, this industry derives protection primarily from intellectual property rights. The article aims to present the significance of this branch of law for the fashion industry, as well as possible protection measures.
Keywords: fashion copyright; intellectual property law; trademark; industrial design; unfair competition